2010
DOI: 10.1177/0145445510390931
|View full text |Cite
|
Sign up to set email alerts
|

Stress Reduction at the Work-Family Interface: Positive Parenting and Self-Efficacy as Mechanisms of Change in Workplace Triple P

Abstract: Workplace Triple P (WPTP) is a group-based parenting skills training specifically designed to meet the needs of employed parents. Several randomized controlled trials have demonstrated the training's efficacy. This study examined possible mechanisms of change that account for the stress reduction effects of this parenting skills training at the work-family interface. It was hypothesized that reductions in dysfunctional parenting (DP) behavior and increases in parental self-efficacy would mediate the stress-red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
1
19
0
2
Order By: Relevance
“…Participating parents most likely differed from our parent population in employment, education, and general feelings of competence. Moreover, Hartung and Hahlweg () studied a universal sample that exhibited less problem behavior than our indicated sample. It has previously been reported that child problem behavior decreases parents' feelings of self‐efficacy (Jones & Prinz, ), suggesting that self‐efficacy in our sample might have been lower than in previous studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Participating parents most likely differed from our parent population in employment, education, and general feelings of competence. Moreover, Hartung and Hahlweg () studied a universal sample that exhibited less problem behavior than our indicated sample. It has previously been reported that child problem behavior decreases parents' feelings of self‐efficacy (Jones & Prinz, ), suggesting that self‐efficacy in our sample might have been lower than in previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that parental feelings of self‐efficacy mediate program efficacy in PMT. Parent training (Triple P) increased parental self‐efficacy, which subsequently changed parenting strategies (Hartung & Hahlweg, ). Similarly, in the Home‐Start Parenting Program, changes in parenting were predicted by changes in maternal sense of competence (Deković et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…While provided as a benefit through their organization, external organizational support offers new mothers a potentially greater level of comfort in talking about their fears, guilt, and other emotions related to motherhood and work–family balance with someone outside of their organization. For example, a program called Workplace Triple P (Positive Parenting Program) encompasses group‐based parenting skills training and support geared toward meeting the needs of employed parents in an effort to reduce stress and improve parenting skills (Hartung & Hahlweg, ). Additionally, some firms offer externally provided “return‐to‐work” programs to reduce the stress new parents may experience and, thus, optimize the retention among this group of workers (Huang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Key theoretical mechanisms, based on self-regulatory processes, include parental self-efficacy, personal agency, independent problem solving, and self-sufficiency (Karoly, 1993), while other cognitive and affective domains have been posited, such as changes in parenting knowledge, attributions, expectations and beliefs, and emotional regulation (Sanders & Morawska, 2005). Prior mediation studies using Triple P are informative and have provided some support for causal hypotheses, such as the link between self-efficacy and parenting stress (Hartung & Hahlweg, 2011), and between parenting competence and reductions in dysfunctional parenting styles (McTaggart & Sanders, 2007). However, the relative importance of these putative processes is not clear, nor whether similar mediating processes will be evident during participation in an online program, or if self-directed versus practitioner-supported delivery work through different mechanisms.…”
Section: Exploring the Mechanisms Of Parenting Change Through Web-basmentioning
confidence: 99%
“…Within the context of Triple P, McTaggart and Sanders (2007) showed that parental self-efficacy partially mediated change in dysfunctional parenting styles, while a study of Workplace Triple P showed reductions in dysfunctional parenting practices mediated change in individual stress-levels, which in turn mediated work-related stress (Hartung & Hahlweg, 2011). Furthermore, Sanders and Morawska (2005) examined the links between parenting knowledge, competence and self-efficacy, and identified a range of possible mechanisms such as parental attributions, beliefs, expectations, self-efficacy, social supports, and self-regulation as potential candidates for further study.…”
Section: Program: An Exploratory Factor Analysismentioning
confidence: 99%